PENGARUH PAPARAN CH4 DAN H2S TERHADAP KELUHAN GANGGUAN PERNAPASAN PEMULUNG DI TPA MRICAN KABUPATEN PONOROGO - Ratih Andhika Akbar (Journal of Industrial Hygiene and Occupational Health, 2016)
Methane (CH4) as gases with the highest concentration at a landfill and Hydrogen Sulfide (H2S) as a very pungent odor contributor due to bacterial or chemical processes will directly have impacts on scavengers who daily work at a landfill. When the concentration of CH4 and H2S gases at the landfill exceeds the standard quality and is inhaled by scavengers will cause respiratory disorder complaints such as cough, chest pain, and shortness of breath. The objective of this research is to analyze the effect of CH4 and H2S exposure on respiratory disorder complaints of scavengers at landfill of Mrican, Ponorogo Regency. This research used the observational analytical method with the cross-sectional design. Its population was 32 scavengers. The samples of research were taken by using the total sampling technique. The effect of CH4 and H2S gases was examined by a means of Fisher test. The measurement of correlational strength between the dependent and independent variables used the Odds Ratio (RO). The concentration of CH4 gas in active and passive zones in the morning and in the afternoon exceeds the standard quality with concentration of 0,11 %. The concentrations of H2S gas are 0,024 ppm in the active zone and 0,022 ppm in the passive zone respectively, which exceed the standard quality. The result of  Fisher test shows that there is an effect of CH4 and H2S gas exposure on the respiratory disorder complaints with p = 0,015 and 0,038 for each variable respectively (p < 0,05). The value of RO for CH4 gas is 0,101 with the probability to suffer from respiratory disorder complaints of 9,2 %. Meanwhile, the value of RO for H2S is 0,137 with the probability to suffer from respiratory disorder complaints of 12 %. Keyword: CH4; H2S; landfiill; respiratory disorder complaint; scavengers